(untitled) (Nigerian Dental Journal, 2024)
ABSTRACT Background: Dental emergence staging involves the utilization of a group of teeth to categorize the dentition into deciduous, mixed, adolescent and permanent. The various stages serve as guides for clinical intervention. Aims: This present study was conducted to determine the onset of the various dentition stages among a group of Nigeria children. Materials and method: it was a cross-sectional descriptive study and data were collected over a fourteen-month period among clinically healthy 424 participants comprising of 186 male and 238 females aged 4-15 years and analysed using SPSS statistics 22.0. The mean ages of onset of the various dental stages, the overall dental stages and the dental stages of each jaw were compared according to gender using unpaired t-test. Statistical significance level was set at P<0.05. Result: The average age of the fully established deciduous dentition was 4.61 ± 0.79 years among females and 5.00 ± 1.16 years in males, p=0.153. Females were also observed to have attained early mixed dentition, late mixed dentition and adolescent dentition earlier than male participants. The average age of the fully erupted first and second molars were 9.76 ±2.36 years and 13.06 ± 1.71 years respectively with female participants observed to have attained each of the stages earlier than male participants, P>0.05. Conclusion: The results shows that female participants attained early mixed dentition, late mixed dentition and adolescent dentition earlier than males. However, males had early attainment of the intermediate mixed dentition. The average age of the fully erupted first and second permanent molars which also tend to have occurred earlier among the females. Therefore, there is the need to individualized staging of the dentition stage to guide the appropriate timing of treatment intervention. Keywords: Dental emergence, Dental eruption, Dentition stage